МИР ГЕРОЕВ ДОСТОЕВСКОГО В ИНТЕРПРЕТАЦИИ М. БАХТИНА - Повторева, С. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Автор статьи рассматривает ряд антропологических идей М. Бахтина, сделавших его интерпретацию творчества Ф. Достоевского новаторской. Речь идет о принципах незавершимости, полифонии и диалогизма, открытие которых позволяет глубже понять не только мир героев Достоевского, но экзистенциальные основания и проблематичность бытия человека в современном мире. Показано, что произведения М. Бахтина открыли небывалые горизонты для гуманитарных исследований. В статье демонстрируется, что подходы М. Бахтина к анализу творчества Ф. Достоевского нашли понимание и воплощение в работах славянских философов, а также представителей западной мысли (в особенности в постструктурализме). Світлана Повторева. Світ героїв Достоєвського в інтерпретації М.Бахтіна. Автор статті розглядає ряд антропологічних ідей М.Бахтіна, що зробили його інтерпретацію творчості Ф.Достоєвського новаторською. Йдеться про принципи незавершимості, поліфонії та діалогізму, відкриття яких дозволяє більш глибоко зрозуміти не лише світ героїв Достоєвського, але й екзистенціальні засади і проблематичність буття людини у сучасному світі. Показано, що твори М.Бахтіна відрили небувалі горизонти для гуманітарних досліджень. У статті демонструється, що підходи М.Бахтіна до аналізу творчості Ф.Достоєвського знайшли розуміння і втілення у роботах слов’янських філософів, а також представників західної думки (особливо у постструктуралізмі). Ключові слова: діалогізм, монологізм, незавершимість, поліфонія, постструктуралізм. Svetlana Povtoreva. The World of F.Dostoyevsky’s Characters by M.Bachtin’s Interpretation. The author of the article examines some anthropological ideas of M.Bachtin, who interpreted works of F.Dostoyevsky an innovatory way. The principles of unaccomlishness, polyphonics and dialogism, which M.Bachtin applies allows understanding better not only the spiritual world of F. Dostoyevsky’s characters, but also the existential basis and unsteadiness of human being in the modern world. In accordance with the principle of unaccomlishness the characters of his works are independent alive persons, which have the equal rights with the author. So he cannot to describe (show) the finished picture of their lives and consciousness. In the Dostoyevsky’s novels M.Bachtin discovers the person as another alive and enjoying equal rights consciousness, other people’s truth, which is oppositely of author’s activity. Another principle Dostoyevsky’s works – polyphonic – gives him the opportunity to destruct monologue structure of art’s representation of the world. In the polyphonic novel the personages are in constantly communication, have many voices. Third Dostoyevsky’s discovery (dialogism) was the instrument of investigation the internal world of people. M.Bachtin accents that the truth is not in the head of one man, but it birth between some people, in the process of their communication. The works of M.Bachtin open wide horizons for humanitarian investigations. The article demonstrates that M.Bachtin’s approach to F.Dostoyevsky’s works was supported by Slavic and by some representatives of western philosophers (especially by poststructuralists). Keywords: dialogism, monologism, poststructuralism, polyphonics, unaccomlishness , transgression.